Integration in Multiple-Document Comprehension: A Natural Language Processing Approach. Issue 5 (3rd July 2022) - Sonia, Allison N.; Magliano, Joseph P.; McCarthy, Kathryn S.; Creer, Sarah D.; McNamara, Danielle S.; Allen, Laura, K.
ABSTRACT: The constructed responses individuals generate while reading can provide insights into their coherence-building processes. The current study examined how the cohesion of constructed responses relates to performance on an integrated writing task. Participants ( N = 95) completed a multiple document reading task wherein they were prompted to think aloud, self-explain, or evaluate the sources while reading and then write an integrated essay based on their reading. Natural Language Processing techniques were used to analyze the cohesion of the constructed responses at both within- and across-text levels. Both within- and across-text cohesion indices were positively related to essay quality; however, across-text cohesion indices exhibited stronger effects. Overall, this study provides evidence that the cohesion of constructed responses can serve as a proxy of the coherence of the mental representations that readers construct during multiple document processing.